2021
DOI: 10.1094/pdis-03-21-0625-sc
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Xylella fastidiosa is the Causal Agent of Almond Leaf Scorch Disease in Alicante, Mainland Spain (Iberian Peninsula)

Abstract: In 2017, Xylella fastidiosa, a quarantine plant pathogenic bacterium in Europe, was detected in almond trees associated to leaf scorch symptoms in Alicante, a Mediterranean area in southeastern mainland Spain. The bacterium was detected by serological and molecular techniques, isolated in axenic culture from diseased almond trees, and identified as X. fastidiosa subsp. multiplex ST6. Inoculation experiments on almond plants in greenhouse trials with a characterized strain of X. fastidiosa subsp. multiplex ST6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…As expected, using NGS analysis we identified four different ASVs belonging to X. fastidiosa that correspond to the subsp. multiplex associated to ALSD in the DA of the Valencian Community, in the province of Alicante (Spain) ( Arias-Giraldo et al, 2020 ; Marco-Noales et al, 2021 ). Additionally, we found good agreement between X. fastidiosa reads obtained by NGS analysis and the Cq values obtained by the two qPCR protocols used to detect X. fastidiosa infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As expected, using NGS analysis we identified four different ASVs belonging to X. fastidiosa that correspond to the subsp. multiplex associated to ALSD in the DA of the Valencian Community, in the province of Alicante (Spain) ( Arias-Giraldo et al, 2020 ; Marco-Noales et al, 2021 ). Additionally, we found good agreement between X. fastidiosa reads obtained by NGS analysis and the Cq values obtained by the two qPCR protocols used to detect X. fastidiosa infection.…”
Section: Discussionmentioning
confidence: 99%
“…pauca ST80 on the island of Ibiza ( Delbianco et al, 2022 ). Simultaneously to the outbreak detected in Majorca, in the summer of 2017, the symptoms of ALSD were also observed for the first time in mainland Spain on 30-year-old almond trees in several orchards in the municipality El Castell de Guadalest of Alicante province, in the Eastern coast of the Iberian Peninsula ( Marco-Noales et al, 2021 ). Currently, the X. fastidiosa demarcated area (DA) in the Valencian Community covers an extension of >136,200 ha (>135,000 in Alicante province and >1,200 in Valencia province).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…pauca ST53, in Lecce (Morelli et al, 2021;Saponari et al, 2013), and other with ALS, caused by X. fastidiosa subsp. multiplex ST6, in Alicante (Landa et al, 2020;Marco-Noales et al, 2021). The climate covariates presented low variabilities and were not relevant in the resulting models, so they were not related with the distribution of X. fastidiosa in the study areas.…”
Section: Epidemiological Models To Assist Outbreak Response Programme...mentioning
confidence: 96%
“…On the other hand, Davis et al (1980) observed that almond trees inoculated in the spring (March) and summer (June) showed symptoms 3 months later. More recently, Marco-Noales et al (2021) observed disease symptoms a year after inoculation.…”
Section: Symptoms Subspecies and Sequence Types Almond Leaf Scorch Diseasementioning
confidence: 98%